Technological Potential of Non-Saccharomyces yeasts (Research, Society and Development, 2022)
Beer is a beverage made up of water, malt, hops and yeast. Yeast is the main transforming agent, converting sugars into ethanol, CO2 and a series of compounds providing flavor and aroma. Saccharomyces yeasts stand out as the most used by the industry. With the growing number of beer consumers and the great diversity of flavors, the number of breweries is also increasing. The objective of this research was to evaluate the biotechnological potential of non-Saccharomyces yeasts kept in collections. The biotechnological potential to be used in the industry was evaluated. Biochemical differentiation of strains into ALE and LAGER, ethanol tolerance and yeast flocculation potential were performed. The results obtained showed that the yeasts presented a potential to be applied in fermentation processes. All yeasts used in the biochemical differentiation tests showed results that allow classifying them as LAGER type yeasts. In the flocculation test, all yeasts were found to be industrial yeasts according to the classification criteria of the American Society of Brewing Chemistry. In the evaluation of ethanol tolerance at concentrations of 10%, 15% and 20%, only the yeast used in the control showed tolerance to 15% ethanol, the yeast Saccharomyces cerevisiae obtained from the culture collection showed tolerance to 10% ethanol, and the others did not. showed tolerance to ethanol at the concentrations used. The study presented promising results suggesting that yeasts can be used in fermentation processes, being necessary to carry out further investigations to certify the real potential of these yeasts.